Analysis of the implementation of the recommendations of international organizations on the status of teachers in the Republic of Kazakhstan - Balmagambetova, V.M.; Kakhanov, A.S. (BULLETIN of L.N. Gumilyov Eurasian National University Law Series, 2024)
The topic of this article is devoted to the study of specialized Kazakh and foreign legal acts, and norms related to the regulation of the status of university teachers. The legal issues of the status of teachers in the system of higher education are becoming relevant worldwide, in all states, including the Republic of Kazakhstan. In this regard, the Republic of Kazakhstan systematically raises the issue of the need to improve the status of teachers of higher education, which affects the quality of higher education. The relevance of the topic is also highlighted by the 1998 World Declaration on Higher Education for the Twenty-First Century. This article presents an analysis of the legislative acts of the Republic of Kazakhstan that regulate the status of teachers of higher education institutions. In addition, the article proposes a new draft of the Kazakh law: "On the status, powers and encouragement of the teacher of higher education institution", in order to improve the status of the country's teaching staff. Features, structure of the status of teachers in the system of higher education are studied in the context of Kazakhstan law and public international law. The recommendations of international organizations in the issue of raising the status of teaching staff have been studied. In addition, some international documents dealing with the status of teachers were analyzed.